SISTEM PAKAR APLIKASI DIAGNOSA PENYAKIT DALAM BERBASIS WEBSITE - Zahra, Haura; Asyhari, Muhammad Fiddiana; Romansah, Romansah (Universitas Palangka Raya, 2024)
An internal medicine expert system is an application designed to assist in the process of diagnosing diseases based on symptoms experienced by patients. In today's digital era, the use of web-based expert systems is growing because it provides wider accessibility to users. This research aims to implement a website-based internal medicine expert system as a diagnosis tool for the general public. This system development method involves the steps of needs analysis, system design, implementation, and evaluation. In the needs analysis phase, data on disease symptoms and related medical information were collected to build the expert system knowledge base. Based on the analysis, a user-friendly website interface was designed as well as an algorithm for matching symptoms with corresponding diseases. Implementation was done using web technologies such as HTML, CSS, and JavaScript to build an interactive and responsive user interface. System evaluation was conducted through functionality and diagnosis accuracy trials involving a number of sample disease cases. The evaluation results show that the web-based internal medicine expert system is able to provide a fairly accurate diagnosis according to the symptoms entered by the user. Thus, the implementation of this system can be an effective solution in helping people to make an initial diagnosis of the disease.